2012
DOI: 10.1016/j.geoderma.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Vertisols of tropical Indian environments: Pedology and edaphology

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 81 publications
(196 reference statements)
1
72
0
7
Order By: Relevance
“…Although selected pedogenic processes such as laterization, hard setting, fragipan formation and claypan formation are hitherto considered as natural soil degradation processes as they lead to less desirable physical and chemical conditions, causing degradation of soils 7,8 , the majority of the information on soil degradation at national 9,10 , regional 11 or international level 12,13 has focused only on anthropogenic degradation. However, a few recent reports on major soil types (Indo-Gangetic Plains or IGP, red ferruginous and deep black soils) at the National Bureau of Soil Survey and Land Use Planning (NBSS&LUP, ICAR), Nagpur, India showed that the development of sodicity and accumulation of relatively higher amounts of exchangeable Mg (EMP) than that of exchangeable Ca (ECP) in soils are also a natural process of soil degradation in the SAT climatic conditions 1,3,[14][15][16][17][18][19][20] .…”
Section: Definition Processes and Factors Of Soil Degradationmentioning
confidence: 99%
See 4 more Smart Citations
“…Although selected pedogenic processes such as laterization, hard setting, fragipan formation and claypan formation are hitherto considered as natural soil degradation processes as they lead to less desirable physical and chemical conditions, causing degradation of soils 7,8 , the majority of the information on soil degradation at national 9,10 , regional 11 or international level 12,13 has focused only on anthropogenic degradation. However, a few recent reports on major soil types (Indo-Gangetic Plains or IGP, red ferruginous and deep black soils) at the National Bureau of Soil Survey and Land Use Planning (NBSS&LUP, ICAR), Nagpur, India showed that the development of sodicity and accumulation of relatively higher amounts of exchangeable Mg (EMP) than that of exchangeable Ca (ECP) in soils are also a natural process of soil degradation in the SAT climatic conditions 1,3,[14][15][16][17][18][19][20] .…”
Section: Definition Processes and Factors Of Soil Degradationmentioning
confidence: 99%
“…It was, however, envisaged that if adverse changes occur in some areas, then these processes will certainly constitute a most serious form of humaninduced degradation of natural resources. Climate change from the humid to semi-arid did occur during the late Holocene in major parts of the Indian subcontinent [3][4][5] . It is quite likely, therefore, that the current aridic environment prevailing in many parts of the world, including India, might create adverse physical and chemical environment, leading to reduced productivity of soils.…”
Section: Neotectonic-climate Linked and Mineral Induced Natural Chemimentioning
confidence: 99%
See 3 more Smart Citations